The impact of affective skills toward on the mathematics learning outcomes at senior high school students - Wahyuddin Wahyuddin; Nur Qalbi Rusdin; Muhammad Awal Nur (Jurnal Elemen, 2022)
Affective skill is one of the factors that students must possess and are the key to successful learning; affective skills are also one of the skills needed in the world of work in the future. This research aimed to analyze the influence of affective skills and their influence on learning outcomes and the dominant influencing variables. This quantitative survey was conducted in January-March 2021, involving 155 students (61 males and 94 females). The variables consisted of exogenous variables, namely affective skills (math interest, math anxiety, math self-efficacy, beliefs, and math attitude), while endogenous variables are learning outcomes. The instrument used to measure exogenous variables were questionnaires including math interest, math anxiety, math self-efficacy, beliefs, and math attitude that met the validity and reliability tests. While the endogenous variable, namely understanding results obtained from the value of documentation of student learning outcomes at school. The data was processed by descriptive and inferential analysis through structural equation modeling (SEM). The study results concluded that math self-efficacy and math attitude were in the high category, beliefs and math interests were suitable. Math anxiety was of a low sort. Furthermore, math interest, math self-efficacy, beliefs, and math attitude were found to have no significant effect on learning outcomes, which means that math interest, self-efficacy, ideas, and math attitude were not sufficient to provide evidence that they could significantly influence learning outcomes.